2017
DOI: 10.1002/2017jd027476
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Regional Reanalysis in China: Evaluation of 1 Year Period Experiments

Abstract: Globally, reanalysis data sets are widely used in assessing climate change, validating numerical models, and understanding the interactions between the components of a climate system. However, due to the relatively coarse resolution, most global reanalysis data sets are not suitable to apply at the local and regional scales directly with the inadequate descriptions of mesoscale systems and climatic extreme incidents such as mesoscale convective systems, squall lines, tropical cyclones, regional droughts, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Model evaluation was carried out as shown in Figure 4 (monthly mean) and Figure 5 (hourly scale). A general agreement is found between the monthly mean air temperatures (2 m level result) in the EXP_2008 simulation and the observations at the nine meteorological stations within the model domain (Figure 4), with the R 2 value of around 0.99 and a mean bias of −0.74 • C. This result is consistent with the WRF simulation by Zhang, et al [52] which showed a cold bias between 1.0 • C and 1.5 • C for the whole of China. The root mean square error (RMSE) is 1.76 • C, slightly better than the result (1.92 • C) obtained by Cao, et al [20].…”
Section: Model Evaluationsupporting
confidence: 88%
See 2 more Smart Citations
“…Model evaluation was carried out as shown in Figure 4 (monthly mean) and Figure 5 (hourly scale). A general agreement is found between the monthly mean air temperatures (2 m level result) in the EXP_2008 simulation and the observations at the nine meteorological stations within the model domain (Figure 4), with the R 2 value of around 0.99 and a mean bias of −0.74 • C. This result is consistent with the WRF simulation by Zhang, et al [52] which showed a cold bias between 1.0 • C and 1.5 • C for the whole of China. The root mean square error (RMSE) is 1.76 • C, slightly better than the result (1.92 • C) obtained by Cao, et al [20].…”
Section: Model Evaluationsupporting
confidence: 88%
“…The root mean square error (RMSE) is 1.76 • C, slightly better than the result (1.92 • C) obtained by Cao, et al [20]. In the summer, the RMSEs, ranging from 0.94 (June) to 1.33 • C (July), are smaller than the results of Zhang, et al [52] (ranging from 1 to 2.5 • C). In the winter, the RMSEs range from 1.64 (January) to 2.39 • C (November).…”
Section: Model Evaluationmentioning
confidence: 54%
See 1 more Smart Citation
“…Over TP, WRF-driven regional reanalysis shows advantage in simulating precipitation compared to ERA5 (He et al, 2019). The ability of such global reanalysis datasets in depicting regional-scale, complex terrain climate and diurnal-scale variability requires further evaluation and improvement (von Storch, 1999;Sotillo et al, 2005;Bromwich et al, 2016;Zhang et al, 2017). Thus, long-term reanalysis datasets with higher spatial and temporal resolutions are still in need for regional climate researches and investigating phenomena such as extreme rainfall events and mesoscale weather systems.…”
Section: Introductionmentioning
confidence: 99%
“…The East Asia Regional Reanalysis (Yang & Kim, , ) was developed using a four‐dimensional variational (4DVAR) data assimilation technique (Courtier et al, ; Rabier et al, ) by the Korea Meteorological Administration. Zhang et al () also produced a competitive regional reanalysis over mainland China by using the Gridpoint Statistical Interpolation data assimilation system and the Advanced Research WRF (ARW‐WRF; Skamarock et al, ) model. Recently, the regional Indian Monsoon Data Assimilation and Analysis (Mahmood et al, , ), with an emphasis of support in the study of the Asian monsoon characteristics over the Indian subcontinent, has been developed using the 4DVAR method by the Met Office, the National Centre for Medium Range Weather Forecasting, and the India Meteorological Department.…”
Section: Introductionmentioning
confidence: 99%